2019
DOI: 10.1007/s10404-019-2283-1
|View full text |Cite
|
Sign up to set email alerts
|

Convection–diffusion molecular transport in a microfluidic bilayer device with a porous membrane

Abstract: The field of human cell research is rapidly changing due to the introduction of microphysiological systems (MPSs), which commonly feature two stacked microchannels separated by a porous membrane for in-vitro barrier modeling. An essential component to adequately representing a subset of human organ or tissue functions in these microfluidic systems is the concentration distribution of the bio-species involved. In particular, when different cell types are cultured, a delicate balance between media mixing and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Epithelial and endothelial cell layers were cultured in the transwells inserts and microfluidic devices to characterize the permeability of various bio-species based on their concentration measurements. The experimental error analysis associated with these measurements has been reported elsewhere [28].…”
Section: Methodsmentioning
confidence: 99%
“…Epithelial and endothelial cell layers were cultured in the transwells inserts and microfluidic devices to characterize the permeability of various bio-species based on their concentration measurements. The experimental error analysis associated with these measurements has been reported elsewhere [28].…”
Section: Methodsmentioning
confidence: 99%
“…[ 257 ] An essential component for adequately representing a subset of human organ or tissue functions in these microfluidic organ‐on‐a‐chip systems is the concentration distribution of the bioactive compounds involved, especially the delicate balance between media mixing and cellular signaling for long‐term maintenance of the multiple cell type coculture. [ 288 ] Experimental and numerical studies of the molecular concentration distributions resulting from convective‐diffusive mass transport in both microchannels have been conducted by analyzing the effects of media flow rate and direction, separation membrane porosity, microchannel dimensions, and molecular size. [ 289 ]…”
Section: Integration With Emerging Technologiesmentioning
confidence: 99%
“…According to their research objectives, these studies follow two main perspectives; Namely, the Eulerian approach, which focuses on the concentration of particles considering the problem governed by typical convection-diffusion phenomena, and the Lagrangian approach that deals with individual particles, tracing the trajectory of each particle separately. For instance, Frost et al [18] numerically investigated the effect of a porous membrane, modeled by molecular diffusivity, on the molecular convection-diffusion transport in a bilayer microfluidic device. Their results showed that the molecular concentration at the outlet of the bottom channel increased by membrane porosity augmentation, while it was invertedly affected by the upper channel height.…”
Section: Introductionmentioning
confidence: 99%